Pengembangan Sistem Portal Covid berbasis Website menggunakan Framework Laravel - Abdillah Ali; Fajar Pradana; Denny Sagita Rusdianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
At the end of 2019, the first case of pneumonia was reported in the city of Wuhan, Hubei Province. From 18 to 29 December 2019, at least five patients were treated for suspected Coronavirus Disease 2019 (COVID-19). The spread of this disease continues to spread to Indonesia. There are three things that underlie the rapidly increasing number of COVID-19 cases, namely finding cases as early as possible, testing and contact tracing. Finding cases as early as possible will prevent COVID-19 infection from getting worse. The development of the covid portal system in this research is to accelerate case discovery as early as possible. The system development in this research uses the Waterfall method. The research stages start from literature study, needs analysis, design, implementation, testing, and conclusion. The developed web-based system is implemented using the Laravel framework with the MVC development pattern. The system is also equipped with health facility data presented in the form of a map which is implemented using the Here Maps API. The testing method used is the method of white-box testing and black-box testing. The white-box testing method is used for unit testing and integration testing with 100% valid test results. The black-box testing method is used in validation testing with 100% valid test results. Non-functional testing is carried out by testing compatibility requirements using a testing tool called sortSite on several browsers with 100% valid results.